Evaluation of plasma IL-21 as a potential biomarker for type 1 diabetes progression - Schroderus, Anna-Mari; Poorbaugh, Josh; McElyea, Samantha; Beasley, Stephanie; Zhang, Lin; Näntö-Salonen, Kirsti; Rintamäki, Reeta; Pihlajamäki, Jussi; Knip, Mikael; Veijola, Riitta; Toppari, Jorma; Ilonen, Jorma; et al. (Frontiers in Immunology, 2023)
IL-21 is a multifunctional cytokine linked with the pathophysiology of several autoimmune diseases, including type 1 diabetes. In this study, our aim was to examine plasma IL-21 levels in individuals at different stages of type 1 diabetes progression. We measured plasma IL-21 levels, as well as levels of other key pro-inflammatory cytokines (IL-17A, TNF-α and IL-6), from 37 adults with established type 1 diabetes and 46 healthy age-matched adult controls, as well as from 53 children with newly diagnosed type 1 diabetes, 48 at-risk children positive for type 1 diabetes-associated autoantibodies and 123 healthy age-matched pediatric controls using the ultrasensitive Quanterix SiMoA technology. Adults with established type 1 diabetes had higher plasma IL-21 levels compared to healthy controls. However, the plasma IL-21 levels showed no statistically significant correlation with clinical variables, such as BMI, C-peptide, HbA1c, or hsCRP levels, evaluated in parallel. In children, plasma IL-21 levels were almost ten times higher than in adults. However, no significant differences in plasma IL-21 levels were detected between healthy children, autoantibody-positive at-risk children, and children with newly diagnosed type 1 diabetes. In conclusion, plasma IL-21 levels in adults with established type 1 diabetes were increased, which may be associated with autoimmunity. The physiologically high plasma IL-21 levels in children may, however, reduce the potential of IL-21 as a biomarker for autoimmunity in pediatric subjects.